Democratic Challenge in Digital Era - Handoyo, Eko (Political Science Program, Universitas Negeri Semarang, 2020)
This article is based on the growing development of social media in the digital era which provides new public spaces for citizens to express themselves and their interactions with fellow citizens in various aspects of life. This article used library research method to answer the changes from procedural democracy to substantial democracy and the way of democratic citizenship through social media. This article revealed that the use of social media is no longer limited to daily needs, however, social media has a significant role in building political culture as well as citizenship issues in society.